Neutrophil-to-Lymphocyte Ratio Predicts COVID-19 Mortality in the Yucatecan Maya Population: A Retrospective Cohort Study - Adriel Ismael Alonso Batun; Vania Janet Tello Romero; Onel Abraham Pacheco Polanco; Nina Mendez-Dominguez (COVID, 2025)
Background: Severe and critical forms of COVID-19 have been associated with high mortality, particularly in vulnerable or underrepresented populations. The neutrophil-to-lymphocyte ratio (NLR) is an emerging inflammatory biomarker that may aid in early risk stratification. Objective: To evaluate the prognostic value of the NLR in hospitalized patients with severe or critical COVID-19 and assess its association with in-hospital mortality in the Yucatecan Maya population of southeastern Mexico. Methods: This retrospective cohort study included 172 adult patients admitted with severe or critical COVID-19 to a tertiary care center in Yucatán, Mexico. Clinical, demographic, and laboratory variables were analyzed. Univariate and multivariate logistic regression were used to identify predictors of in-hospital mortality. ROC analysis determined the optimal NLR threshold. Results: Among the 172 patients, 79 (45.9%) died during hospitalization. Non-survivors exhibited significantly higher NLR values compared to survivors (median 18.4 vs. 6.3; p < 0.001). In multivariate analysis, the NLR remained an independent predictor of mortality (OR 1.66; 95% CI: 1.26–2.17; p < 0.001). The ROC curve showed an AUC of 0. 0.83 for Intensive Care Unit and 903 for in hospital death. Conclusions: In this regional cohort of the Yucatecan Maya population, the NLR was a strong independent predictor of mortality in patients with severe or critical COVID-19. The identified cutoff of the NLR ≥ 9.76 may serve as a valuable, low-cost tool for early risk assessment in similar settings with limited resources.